Distinct roles for motor neuron autophagy early and late in the SOD1(G93A) mouse model of ALS - Rudnick, Noam D. (Proc Natl Acad Sci U S A, 2017)
Mutations in autophagy genes can cause familial and sporadic amyotrophic lateral sclerosis (ALS). However, the role of autophagy in ALS pathogenesis is poorly understood, in part due to the lack of cell type-specific manipulations of this pathway in animal models. Using a mouse model of ALS expressing mutant superoxide dismutase 1 (SOD1(G93A)), we show that motor neurons form large autophagosomes containing ubiquitinated aggregates early in disease progression. To investigate whether this response is protective or detrimental, we generated mice in which the critical autophagy gene Atg7 was specifically disrupted in motor neurons (Atg7 cKO). Atg7 cKO mice were viable but exhibited structural and functional defects at a subset of vulnerable neuromuscular junctions. By crossing Atg7 cKO mice to the SOD1(G93A) mouse model, we found that autophagy inhibition accelerated early neuromuscular denervation of the tibialis anterior muscle and the onset of hindlimb tremor. Surprisingly, however, lifespan was extended in Atg7 cKO; SOD1(G93A) double-mutant mice. Autophagy inhibition did not prevent motor neuron cell death, but it reduced glial inflammation and blocked activation of the stress-related transcription factor c-Jun in spinal interneurons. We conclude that motor neuron autophagy is required to maintain neuromuscular innervation early in disease but eventually acts in a non–cell-autonomous manner to promote disease progression.